Literasi dan aljabar dalam penalaran matematika melalui tes berbasis komputer:Tinjauan literatur sistematis - Fitriyani Fitriyani; Duano Sapta Nusantara; Rohati Rohati; Kgaladi Maphutha (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2026)
This systematic literature review (SLR) aims to analyze and synthesize the role of literacy and algebraic proficiency in predicting students' mathematical reasoning abilities, specifically in the context of the Computer-Based Written Exam (UTBK). The SLR method used in this study is a review of 18 articles, consisting of 11 documents from the Scopus database and 7 from the Google Scholar database, from 2019-2025. Using bibliometric analysis with the VOSviewer application, it shows that students' difficulties often arise at the stage of understanding problem narratives (literacy) before they are able to model and generalize algebra (algebraic literacy), which then leads to their logistical reasoning. However, the existing literature data indicates a research gap because no study has explicitly used structural modeling (SEM) to quantitatively test and validate the causal relationship pathways between these three variables. Therefore, the main recommendation of this study is to develop a rigorous structural model, supported by diagnostic error analysis based on Newman's analysis (NEA), to provide a strong foundation for focused and effective pedagogical interventions